PENGARUH ULASAN ONLINE, KUALITAS PRODUK, DAN PERSEPSI HARGA TERHADAP KEPUTUSAN PEMBELIAN SUNSCREEN AZARINE - Saputri, Dinda Ayu Selviana; Chamidah, Siti; Purwaningrum, Titis (Jurnal Manajemen, 2024)
Goal of the study is to determine how customers' decisions to purchase azarine sunscreen are influenced by online user reviews, perceptions of product quality, and pricing. Therefore, this research can provide a deeper understanding of the factors motivating consumer purchase decisions, particularly among students at Muhammadiyah University of Ponorogo. This research employs a quantitative method, with data collection conducted through questionnaires. The respondents are management students from the 2020-2023 cohorts at Muhammadiyah University of Ponorogo, totaling 80 individuals as calculated using the Heir formula. The study's findings show that the variable Online Customer Reviews had no discernible impact on consumers' decisions to buy Azarine sunscreen, while the variables Product Quality and Price Perception have a significant influence on the purchase decision of Azarine sunscreen.